Avatar, the last airbender. Azula in the spirit temple - Hicks, Faith Erin; Wartman, Peter (Milwaukie, OR : Dark Horse Books, 2023)
Azula continues her destabilizing campaign against the Fire Nation and her brother, Fire Lord Zuko. But after a failed attack on her latest target, Azula finds herself in a mysterious forest temple inhabited by a solitary monk...or is it something more mysterious? Azula must confront her past, and finally face her chance at redemption.
At head of title: Nickelodeon.
Young Adult
Keywords: Avatars (Religion) -- Fiction; Avatars (Religion) -- Comic books, strips, etc; Heroes -- Fiction; Heroes -- Comic books, strips, etc; Magic -- Fiction; Magic -- Comic books, strips, etc; Martial arts -- Fiction; Martial arts -- Comic books, strips, etc; Action and adventure fiction; Fantasy fiction; Graphic novels; Prisoners -- Fiction; Four elements (Philosophy) -- Fiction; Comics (Graphic works)